2022
DOI: 10.1111/pan.14521
|View full text |Cite
|
Sign up to set email alerts
|

Videolaryngoscopes versus direct laryngoscopes in children: Ranking systematic review with network meta‐analyses of randomized clinical trials

Abstract: Background: Videolaryngoscopes improve tracheal intubation in adult patients, but we currently do not know whether they are similarly beneficial for children. We designed this ranking systematic review to compare individual video and direct laryngoscopes for efficacy and safety of orotracheal intubation in children. Methods:We searched PubMed and five other databases on January 27, 2021. We included randomized clinical trials with patients aged ≤18 years, comparing different laryngoscopes for the outcomes: fai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…A major change from the early cohort to the current cohort has been the dramatic increase in standard blade video laryngoscopy. There is a rapidly growing body of evidence that standard blade video laryngoscopy offers improved first attempt success and reduced rates of complications in infants and children with both normal and difficult airway anatomy, 22 , 24 , 25 which aligns with the most recent Cochrane review in adults. 26 Although video systems require a financial investment, these data can support cost effectiveness analysis in improving patient safety.…”
Section: Discussionmentioning
confidence: 80%
“…A major change from the early cohort to the current cohort has been the dramatic increase in standard blade video laryngoscopy. There is a rapidly growing body of evidence that standard blade video laryngoscopy offers improved first attempt success and reduced rates of complications in infants and children with both normal and difficult airway anatomy, 22 , 24 , 25 which aligns with the most recent Cochrane review in adults. 26 Although video systems require a financial investment, these data can support cost effectiveness analysis in improving patient safety.…”
Section: Discussionmentioning
confidence: 80%
“…However, more time for intubation was required for the use of video laryngoscopes because more time is required for the tube to pass through the glottis [6,7]. Reports comparing video laryngoscope models have not discovered a video laryngoscope model evidently advantageous for use in children [11][12][13]. Few studies have used McGRATH™ MAC on infants, especially since blade size 1, which is considered an appropriate size for infants, recently became available.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in TTI was in line with the findings of previous studies, which showed that, in children with difficult airways, the UEscope provided a better glottic view, higher first-attempt success rate, and shorter TTI [ 14 , 17 ]. On the contrary, a recent metanalysis including 46 RCTs of videoscope showed that video laryngoscopes reduced the risk of failed first intubation attempts but did not decrease TTI in children, although every video laryngoscope had a different performance metrics [ 18 ].…”
Section: Discussionmentioning
confidence: 99%